Investigation of olive mill wastewaters treatment by immobilized microalgae - Martins, Bruna da Silva (2018)
During the extraction process of olive oil a large quantity of liquid and solid residues are produced. Nowadays, two-phase and three-phase centrifugation systems are most commonly used. The two-phase centrifugation system reduces the water consumption during the process and practically integrates the three-phase mill wastewater, nevertheless in smaller quantities. The two-phase olive-mill waste presents a slightly acidic pH and a very high content of organic matter, comprising relatively large amounts of lignin, hemicellulose and cellulose, fats, carbohydrates, as well as phenolic compounds [1, 2]. Despite the fact that degradation of olive mill effluents was exhibited in the past [1-3], two-phase olive-mill waste still pose serious problems related with its effective management and safe disposal. Biotreatment of wastes water using living organisms is an environmentally friendly, relatively simple and cost-effective alternative to physico-chemical processes. Previous work was shown that Chlorella vulgaris, a single-cell Chlorophyceae, was the ability to growth in medium supplemented with several plant extracts rich in phenolic compounds [5]. Therefore, the aim of this work was evaluate the ability of immobilized C. vulgaris to remove phenolics compounds from olive mill wastewaters and assess their potential bioremediation by evaluating toxicity on final treated effluent.